2010
DOI: 10.1016/j.niox.2009.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Role of soluble guanylyl cyclase–cyclic GMP signaling in tumor cell proliferation

Abstract: Our previous studies demonstrate a differential expression of nitric oxide (NO) signaling components in ES cells and our recent study demonstrated an enhanced differentiation of ES cells into myocardial cells with NO donors and soluble guanylyl cyclase (sGC) activators. Since NO-cGMP pathway exhibits a diverse role in cancer, we were interested in evaluating the role of the NO receptor sGC and other components of the pathway in regulation of the tumor cell proliferation. Our results demonstrate a differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 39 publications
5
44
0
3
Order By: Relevance
“…sGC are a family of proteins composed of membrane-bound and soluble isoforms and expressed in virtually all cell types [43]. sGC catalyze conversion of the purine nucleoside guanosine-5′-triphosphate to cGMP in response to various messengers such as peptide ligands, calcium influx, and NO [44].…”
Section: Guanylyl Cyclase and Signaling By Cyclic Guanosine Monophospmentioning
confidence: 99%
“…sGC are a family of proteins composed of membrane-bound and soluble isoforms and expressed in virtually all cell types [43]. sGC catalyze conversion of the purine nucleoside guanosine-5′-triphosphate to cGMP in response to various messengers such as peptide ligands, calcium influx, and NO [44].…”
Section: Guanylyl Cyclase and Signaling By Cyclic Guanosine Monophospmentioning
confidence: 99%
“…Synergistic Effect of CN2-Cbi and BAY41-2272 in Intact Cells and Isolated Aorta. We tested whether CN2-Cbi activates sGC in intact breast cancer MDA468 cells, previously shown to express functional sGC (Mujoo et al, 2010). An increased intracellular cGMP level was observed when these cells were exposed to 100 M CN2-Cbi (Fig.…”
Section: Novel Regulatory Site For No Receptor 727mentioning
confidence: 99%
“…It is reported that the enhancement of a soluble form of GUCY1B3 led to the activation of the osteoclasts in the osteolytic bone metastasis process. Moreover, this protein enhances tumor growth of glioma (35) and angiogenesis in both glioma and chorioallantoic membrane (35,36), and plays paradoxical roles in the proliferation of cancer cells (37), suggesting that GUCY1B3 could be involved in bone metastasis.…”
mentioning
confidence: 99%